2010
DOI: 10.1177/0363546510373570
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Noncontact Anterior Cruciate Ligament Injuries

Abstract: Based on when the sudden changes in joint angular motion and the peak vertical ground-reaction force occurred, it is likely that the anterior cruciate ligament injury occurred approximately 40 milliseconds after IC. The kinematic patterns were surprisingly consistent among the 10 cases. All players had immediate valgus motion within 40 milliseconds after IC. Moreover, the tibia rotated internally during the first 40 milliseconds and then external rotation was observed, possibly after the anterior cruciate liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
320
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 719 publications
(346 citation statements)
references
References 42 publications
(71 reference statements)
23
320
1
2
Order By: Relevance
“…Mizuno et al [17], Horton and Hall [18] and Koga et al, [19] documented that increases in non-sagittal rotations at the hip and knee, which were shown to be significantly greater in the functional and projected techniques, are associated with the a etiology of injury to the lower extremities. Therefore it appears that researchers should carefully consider their choice of hip joint centre location technique when quantifying non-sagittal rotations and selecting clinical normative data, as it may affect the interpretation of their data.…”
Section: Discussionmentioning
confidence: 99%
“…Mizuno et al [17], Horton and Hall [18] and Koga et al, [19] documented that increases in non-sagittal rotations at the hip and knee, which were shown to be significantly greater in the functional and projected techniques, are associated with the a etiology of injury to the lower extremities. Therefore it appears that researchers should carefully consider their choice of hip joint centre location technique when quantifying non-sagittal rotations and selecting clinical normative data, as it may affect the interpretation of their data.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for investigating frontal plane knee kinematics and kinetics is that these variables have previously been shown to predict ACL injuries in female athletes 14 and that a valgus collapse has been identified as a part of the ACL injury mechanism. 5,15,18,28 In addition, existing screening tools developed to identify knee injury risk have focused on frontal plane knee kinematics and kinetics. 10,27,29 Although the real-time assessment of knee control appears to be promising for large-scale screening of athletes, there is a need to investigate the predictive value of such screening for knee injuries.…”
Section: Discussion Tmentioning
confidence: 99%
“…[ research report ] E xcessive knee valgus motion has been identified as contributing to noncontact anterior cruciate ligament (ACL) injuries 15,18,28 and is visually associated with a medial collapse of the knee during dynamic tasks. Greater knee valgus angles, side-to-side differences in knee valgus, 12 and lower hip and knee flexion angles 21 have been reported to be more common in females compared to males.…”
mentioning
confidence: 99%
“…It is under these dynamic conditions, and in particular within the first 30 to 50 ms after initial ground contact (Koga et al, 2010), that the ACL appears to be most vulnerable to injury from a biomechanical perspective. Females are believed mitigate ground reaction force at the knees in a different manner than their male counterparts, particularly in the frontal and sagittal planes (Hewett et al, 2004Ford et al, 2005b;Hewett, 2008).…”
Section: Introductionmentioning
confidence: 99%